Waqf Instruments for Construction Contract: An Analysis of Structure - Abdullaah Jalil; Asharaf Mohd Ramli (Universiti Sains Islam Malaysia, 2024)
The waqf instruments for construction and development of property are still underutilized in this country. Taking into consideration the increasing cost of construction and limited sources of funds, the potential of waqf instruments to attract more public funds should not be ignored. Waqf instruments could be developed for financing the development of several institutions such as universities, research centres and et cetera. The paper aims to study and analyze the structure of waqf instruments that could be further developed for construction of potential assets. This includes the risks, parties involved, advantages as well as disadvantages. It is a conceptual paper and the authors apply the inductive and deductive methods as well as analysis of the relevant literatures to reach at the findings. The findings suggest several methods and structures of waqf instruments for future development. It could be significant for those institutions that have planned to apply this concept in the nearest future.